2018
DOI: 10.1002/ejsp.2533
|View full text |Cite
|
Sign up to set email alerts
|

Age‐based stereotype threat and negative outcomes in the workplace: Exploring the role of identity integration

Abstract: Previous studies have shown that the presence of age‐based stereotypes in the workplace is often associated with lower levels of work engagement and adjustment among older employees. This study examines possible mediators and moderators of this relationship using data from a sample of 2,348 older (age > 50) employees at the Italian national rail company. We test a model in which the effects of age‐based stereotype threat on organizational involvement, future time perspective, and psychological well‐being are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 64 publications
3
45
0
Order By: Relevance
“…Previous studies have shown that age‐based stereotype threats can deter older workers from staying in the workforce or hinder their motivation to work (Brooke & Taylor, 2005; Edward & Paccei, 2010; Manzi et al., 2019). In line with this literature, results also show that age‐based discrimination negatively affects these relationships: Perceived discrimination based on age reduces POS's ability to foster involvement both directly and indirectly through organizational identification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that age‐based stereotype threats can deter older workers from staying in the workforce or hinder their motivation to work (Brooke & Taylor, 2005; Edward & Paccei, 2010; Manzi et al., 2019). In line with this literature, results also show that age‐based discrimination negatively affects these relationships: Perceived discrimination based on age reduces POS's ability to foster involvement both directly and indirectly through organizational identification.…”
Section: Discussionmentioning
confidence: 99%
“…Age discrimination has different effects on the worker; for example, it limits the possibilities of accessing the job market, training courses, and career advancement (Cuomo & Mapelli, 2014; Lazazzara & Bombelli, 2011). A small number of studies have demonstrated that age discrimination is able to reduce work commitment, involvement, and job satisfaction (e.g., Bal & Kooji, 2011; Bayl‐Smith & Griffin, 2014; Manzi et al., 2019). Discrimination has effects not only on the person's working life but also on their psychosocial adjustment and health (Casad & Bryant, 2016; von Hippel et al., 2013).…”
Section: The Moderating Role Of Age Discrimination In the Relation Bementioning
confidence: 99%
See 2 more Smart Citations
“…The consequences of encountering ageism in the workplace are widespread with implications for overall and professional well-being (Manzi et al, 2019). Feelings of inadequacy, powerlessness, and social isolation may result from reduced opportunities for training, appraisals, promotion and wage increases, and inclusion (Furunes & Mykletun, 2010).…”
Section: Ageismmentioning
confidence: 99%